Breastfeeding Problems In Teenage Mothers: A Scoping Review - Wulan Wijaya; Ina Sugiharti; Linda Listriyati (STIKes RSPAD RSPAD Gatot Soebroto, 2026)
Background: Breastfeeding practices among teenage mothers are among the lowest globally, despite the increasing proportion of breastfeeding teenage mothers. The impact of breastfeeding teenage mothers who do not breastfeed will cause growth and development delays in infants, lack of bonding (relationship) between mother and infant, and malnutrition in infants. Objective: To examine breastfeeding issues among teenage mothers. Method: This scoping review method consists of several steps, namely identifying scoping review questions, identifying relevant literature sources, selecting literature, compiling, summarizing, and reporting the results. Results: Based on a critical review, 19 articles were obtained. The results of the study found 3 themes, namely low education levels, lack of maternal knowledge about breastfeeding, and lack of support for breastfeeding mothers. Conclusion: Breastfeeding issues among teenage mothers are an important note that must be considered because when a teenager has to become a mother at a young age and they are required to be able to become a mother at a young age. The problems faced by teenage mothers are very diverse. The findings of this study can be used as a basis or input for further researchers to examine more deeply other problems related to breastfeeding among teenage mothers.